2022
DOI: 10.1002/cepa.1806
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of Plate Girders with Intermediate Transverse Stiffeners – Experimental Investigation

Abstract: Transverse stiffeners are used in slender steel plate girders along the span to give web lateral support and increase plate girder shear resistance. According to several studies, transverse stiffeners are primarily engaged in out‐of‐plane bending to laterally limit the edges of the panel as it buckles, rather than axial compression to anchor the tension field. As a result, the axial loading defined in EN 1993‐1‐5 [1] for the design of transverse stiffeners, based on tension field action, is usually deemed to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Recent studies [5][6][7][8] show several results of experimental residual stresses measured after the production of steel plate girders (Fig. 7 (a) e (b)).…”
Section: Residual Stressesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies [5][6][7][8] show several results of experimental residual stresses measured after the production of steel plate girders (Fig. 7 (a) e (b)).…”
Section: Residual Stressesmentioning
confidence: 99%
“…Residual stresses obtained by the sectioning method in the production of beams: (a) G07 and G08, (b) G01 and G02, (c) location of the strain gauges[5][6]. Dimensions in mm…”
mentioning
confidence: 99%
“…A mesh convergence study was conducted to achieve that balance, and the results led to the adoption of a maximum element size of approximately 40x40 mm (about ℎw/25) [32]. The authors' experimental test results were used to validate the model [33].…”
Section: Numerical Modelsmentioning
confidence: 99%
“…They also showed the importance of postbuckling strength in predicting the ultimate shear resistance of stiffened web panels. Nascimento et al [17] gave an insight into the behaviour of the plate girder when it was reinforced with intermediate transverse stiffeners, and they showed that this strengthening contributed signi cantly to limiting lateral panel buckling. Applications of plate girders in seismic-prone areas were the focus of the study by Natesh et al [18], where they used different loading conditions.…”
Section: Introductionmentioning
confidence: 99%